(untitled) (Mongolian Journal of Agricultural Sciences, 2018)
The endogenous jaagsiekte retrovirus (exoJSRV) is integrated into the sheep genome as result of long coevolution of the virus and host and transmitted vertically. The exogenous jaagsiekte retrovirus (endoJSRV) is transmitted from infected sheep and induce ovine pulmonary adenocarcinoma. The differential diagnosis of endoJSRV from the exogenous oncovirus (exoJSRV) is based on unique nucleotide sequences of exoJSRV which is characterized by a digestion of Sca I restriction endonuclease while endo JSRV not. We used the routine diagnostic method for determination of both JSRV in healthy and affected sheep in Mongolia as rest of the world. The 229 bp long PCR product of the Gag region of the virus was amplified in all 81 sheep blood samples from central regions but not digested by Sca I restriction endonuclease which indicate the presence of endoJSRV. The nucleotide sequence of two PCR products of khalkh sheep breed were clustered with viral strains from India and China, respectively. The lung tumor nodule was present in sheep with breeding problems, the hematoxylin and eosin staining of the affected lungs showed strong tumor cell proliferation sites and decreased number of alveoli. The 229 bp PCR product of viral Gag region was digested by Sca I restriction endonuclease which indicate the presence of exogenic JSRV, the oncovirus. The LTR (long terminal repeat) specific PCR of the exoJSRV resulted as positive in two tumor lung samples except non-tumor lung samples and blood samples which validated our results strongly. Монгол хонины эндоген болон уушигны хорт хавдар үүсгэгч онковирусийг ялган оношлосон нь Хураангуй: Хонины эндоген жаагсиектэ ретровирус (Jaagsiekte retrovirus -хJSRV/ЖРВ) нь олон жилийн турш эзэн амьтан болон вирусийн хам эволюцийн явцад эзэн амьтны геномд нэгдэн хонинд удамшдаг болсон байна. Харин ЖРВ-ийн эксоген хэлбэр нь өвчтэй малаас удамшлын бус замаар малд халдварлан уушигны хорт хавдар-аденоматозыг үүсгэдэг онковирус тул ЖРВ-ийн эдгээр хэлбэрийг ялган оношлох нь Монгол орны малын халдварт өвчний үнэн бодит шинжилгээнд зайлшгүй чухал юм. xЖРВ-ийн энэхүү 2 хэлбэр нь хоорондоо төстэй боловч нуклеотидийн дараалал, ялангуяа вирусийн gag хэсгийн 229 хос суурь урттай хэсэг нь Scal эндонуклеаз ферментээр таслагдах эсэхээрээ ялгагддаг нь бусад орны судлаачдын үр дүнгээр тогтоогдсон байна. Бидний цуглуулсан 81 толгой хонины цусны бүх дээжинд 229 хос суурь урттай ДНХ-ийн судал илэрсэн боловч ScaI эндонуклеаз ферментээр хэсэгчлэн таслагдаагүй мөн нуклеоитидийн дарааллыг секвенсингээр тогтооход энэ нь ЖРВ-ийн эндоген хувилбар болох нь нотлогдов. Эмнэлзүйн үзлэгээр амьсгаа нь давхацсан, уушиг хэржигнэсэн шуугиантай хонины уушигны баруун хэлтэр нь 2-3 дахин томорсон, цайвар өнгөтэй болж, хатуурсан, эмгэг бие бүтцийн шинжилгээгээр уушигны цулцангийн ханын шүүрлийн хучуур эс хорт хавдрын эс болон хувирч олшрон үржлийн голомтууд үүсгэн агаарын хийн солилцооны гуурс руу түрэн орж хөхөлгөр ур үүсгэсэн нь ажиглагдав. Энэ судалгаагаар бид эндонуклеаз фермент ашиглан уушигны аденоматоз, хорт хавдар үүсгэгч эксоген ЖРВ-ийн халдварыг бүх хонинд удамшдаг эндоген ЖРВ-ээс ялган оношлох боломжийг нотолсон арга боловсруулав. Мөн LTR хэсгийн өвөрмөц хос праймер ашиглан эксоген ЖРВ-йиг ПГУ-аар илрүүлэх боломжтойг баталгаажуулав. Түлхүүр үг: Жаагсиектэ ретровирус (ЖРВ), онковирус, эксоген ЖРВ, эндоген ЖРВ, хонины уушигны аденоматоз, эндонуклеаз фермент, gag, LTR-long terminal repeat, хөхөлгөр ур